1970
DOI: 10.17667/riim.2018.1/9
|View full text |Cite
|
Sign up to set email alerts
|

A Review Regarding Hand Exoskeleton Technologies for Rehabilitation

Abstract: This paper will be presenting a short review regarding robotic rehabilitation devices. The focus of rehabilitation are aimed for the human hand, mainly for regaining motor functions by the aid of robotics. A comprehensive statistical study will be presented regarding tendencies in the field of rehabilitation,  medical robotics and technologies used for robotic exoskeletons based on existing published papers. A short review on existing practical examples is also presented. In the final part of the papers a shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Gu et al [70] provided valuable information on advances in hardware and software components of hand function rehabilitation systems, integrating gesture recognition devices and artificial intelligence modules. Similarly, Birouas , et al [71] performed a statistical analysis of trends in hand exoskeleton technology, shedding light on current applications and technological advances. In addition, Shahid et al [54] explored the evolution of handheld exoskeleton design, with a specific focus on the incorporation of soft robotics technology in mechanical design, actuation units, and sensory feedback control.…”
Section: Past Reviews Of Soft Hand Exoskeletonsmentioning
confidence: 99%
“…Gu et al [70] provided valuable information on advances in hardware and software components of hand function rehabilitation systems, integrating gesture recognition devices and artificial intelligence modules. Similarly, Birouas , et al [71] performed a statistical analysis of trends in hand exoskeleton technology, shedding light on current applications and technological advances. In addition, Shahid et al [54] explored the evolution of handheld exoskeleton design, with a specific focus on the incorporation of soft robotics technology in mechanical design, actuation units, and sensory feedback control.…”
Section: Past Reviews Of Soft Hand Exoskeletonsmentioning
confidence: 99%
“…Considering a variety of mechanical designs present in this field of research [34], there are a few distinct constructive types that stand out. A solution with direct matching of the finger joint centers (DMFJC) was developed by Chiri et al [6] which can be observed in Figure 2a.…”
Section: General Considerationsmentioning
confidence: 99%
“…The exoskeleton can be classified based on the material used, control method, signal sensing, user training, power transmission, mechanisms, the purpose of use and actuated limb type, as shown in Figure 1. Most of the existing review papers in the field of robotic exoskeletons have Figure 1 Chart showcasing criteria-based classification of exoskeleton narrowed their scope to specific areas such as the lower limb (Srivastava et al, 2020), upper limb (Dubey and Agrawal, 2011), hand (Birouas , et al, 2018;Zhang et al, 2009), shoulder (Cornejo et al, 2021;Majidi and Vatan, 2021), control methods (Abiri et al, 2019;Al-Quraishi et al, 2018;Gu et al, 2021;Miao et al, 2018), exoskeleton recent business developments (Bogue, 2022), wearable exoskeletons (Khakurel et al, 2018) and material used (Hussain et al, 2021). However, the key factors that decide the performance of the exoskeleton are the signalsensing systems, actuators and user training methods.…”
Section: Introductionmentioning
confidence: 99%